Generation of electronic‑waste and its impact on environment and public health in Malaysia - Azad, M.D. Abul Kalam; Islam, Mohd Aminul; Hossin, M M Ismail (Medknow Publications, 2017)
Generation of municipal solid waste as well as electrical and electronic waste (e‑waste) is rapidly increasing in the developing countries, especially in the electronic manufacturing industries which have seen some technological growth within a short timeframe in Malaysia. The purpose of this study is to find out the factors that contribute to the generation of e‑waste and to present the current scenario of Malaysia’s e‑waste management system. The data were collected from the review of various scientific journals and the Department of Environment Malaysia (DOE) which were published and available in online currently. It was observed that recently in Malaysia, the generation of e‑waste is one of the environmental problems in Malaysia. Among other factors, besides industries, use pattern for households, business entities, and institutions are the main contributors of the increased e‑waste generated in Malaysia. DOE reported that, the ratio of bought and possessed electronic appliances among the respondents in Malaysia is not balance. The rate of discarding is higher than possessed rate. Remarkably, in television, 95.6% of the television sets currently possessed are bought from shops, but only 33% of respondents were using it up to now, whereas 62.60% of people are not using their televisions and they have discarded it. Consequently, the discarded rate of other electronic appliances is also almost in the same trend by households, business entities, and institutions in Malaysia. E‑waste containing a lot of dangerous chemicals and metals such as Mercury, Lead, Cadmium, Zinc, and Chromium causes diseases such as brain disorders, kidney, renal, and neurological damage, thus leading to even deaths, learning disabilities, lung damage, mental retardation, behavioral problems, hearing impairment, fragility of the bones, and high blood pressure. It is, therefore, recommended that government should develop the 3Rs initiatives to reduce, reuse, and recycle of e‑waste. At the same time, create awareness among the society to prevent it from the negative impact on the environment through pollution and public health hazards.